Global Governance and Comprehensive Security: Integrative Aspects of Forming a Global Ecosystem of Resilience in Conditions of Hybrid Threats - Karamyshev, Dmytro; Suvorov, Valentyn (Theory and Practice of Public Administration, 2024)
In the article, the concepts of «Comprehensive security» and «Resilience in conditions of hybrid threats» are disclosed in a broad sense. The conceptual approaches, principles and integration aspects of global governance in ensuring comprehensive security are substantiated, and the components of the sustainability assessment system are determined using the example of the OECD countries, which can be the key to building both a global ecosystem of Resilience and a system of national Resilience of Ukraine on the way to becoming a member of the OECD in the conditions hybrid threats.A correlation was made between the assessment of the development of the OECD countries and the assessment of the stability of the OECD countries, as a model by which it is possible to generalize and improve the relevant system of assessment of the OECD countries in the conditions of the conditions hybrid threats.During the evaluation, it is proposed to use the concept of the integrated model of the ecosystem of Resilience (CORE), which can be taken as a basis by the OECD member countries when clarifying the conditions and a set of factors for making strategic decisions regarding development, cooperation and interaction, taking into account comprehensive security and resilience from hybrid effects under conditions of unpredictability.It is emphasized the importance of continuing comprehensive studies of OECD countries based on the already developed methodology with the separation of a separate component that characterizes the state of comprehensive security and resilience of countries, which will make it possible to propose a new integrated evaluation indicator called – The Global Index of Resilience in conditions of hybrid threats (The Global Index of Resilience in Conditions of Hybrid Threats). It has been proven that Ukraine can be an important subject of the implementation of joint projects in the field of integrated security and stability at the OECD level and form a national ecosystem of Resilience in the conditions of hybrid threats, taking into account the above-mentioned guidelines of European integrated security for the benefit of a comprehensive sphere, which is built by integrating its meaningful components taking into account intersubject interaction.